Legal Vacuums in the Management of State Assets from Upstream Oil and Gas Cooperation Contracts - Sumartono, Sumartono; Santiago, Faisal (Journal of Social Science, 2024)
This research examines legal vacuums in the management of state assets derived from Cooperation Contracts (KKKS) in the upstream oil and gas sector in Indonesia. Despite a legal framework established by Law No. 22 of 2001 and Government Regulation No. 35 of 2004, field practices reveal discrepancies between regulations and implementation, leading to difficulties in the recording and reporting of assets, as well as the determination of depreciation values and operational costs. The impact of this legal vacuum not only affects state revenue and transparency but also has significant social and economic implications. Through case study analysis, this research suggests improvements to existing regulations, capacity building for KKKS, and strengthening oversight mechanisms to optimize the management of state assets in the upstream oil and gas sector.